Preparation method and application of heat-resistant transparent polyether amide
By using the reaction and melt polymerization technology of dicarboxylic acid monomer containing ether bonds and diamines in transparent polyamides, the glass transition temperature and transparency of the material are improved, and the existing transparent polyamides are insufficient heat resistance. The problem is that the high transparency and heat resistance are achieved, and are suitable for a variety of high-end applications.
Patent Information
- Application Number
- CN202310482017.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The existing industrial transparent polyamide products have poor heat resistance, low glass transition temperature (Tg), and low thermal stability, making it difficult to meet the simultaneous application needs of high transparency and heat resistance.
The dicarboxylic acid monomer containing ether bonds reacts with diamines in a solvent to form a salt, and heat-resistant transparent polyether amides are prepared by melt polymerization or copolymerization to improve its glass transition temperature and transparency, and enhance the heat resistance of the material. sex.
The prepared transparent polyether amide has high transparency (the light transmittance can reach 90.9% under visible light of 560nm) and good heat resistance (the 5% thermal decomposition temperature can reach above 465℃ under N2 atmosphere), and is suitable for optical instruments. , pressure-resistant windows and other fields.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of transparent polyamide materials, and in particular relates to a preparation method and application of heat-resistant transparent polyether amide. Background Art
[0002] Polyamide (PA), commonly known as nylon, was developed and industrialized by WH Carothers of the DuPont Central Research Institute in the United States in the 1930s. In the early days, it was mainly used as a spinning raw material. It was used as an engineering plastic after the 1950s. With the rapid development of application fields such as automobile industry, electronics, transportation, machinery, aerospace and various daily industries, its production and demand have ranked first among the five major engineering plastics.
[0003] Transparent polyamide is an amorphous or microcrystalline thermoplastic material. It is a polyamide variety with extremely high transmittance to visible light. Its transmittance can reach more than 90%. It is a polymer material with excellent comprehensive performance. Transparent polyamide not only has the advantages of high mechanical strength, good thermal stability, excellent corrosion resistance, low water absorption, excellent transparency, etc., but also has the advantages of easy molding and processing, good dimensional stability, etc. It is widely used in optical devices, medicine and hygiene, cosmetics, kitchen utensils, electrical equipment and mechanical containers.
[0004] The first transparent polyamide prepared and industrialized internationally was Trogamid T developed by Dynamit Nobel in the 1960s. Subsequently, EMS of Switzerland, Arkema of France, DuPont of the United States, and Mitsubishi Chemical of Japan all produced transparent polyamides of different grades. U.S. Patents US5886087A, European Patents EP2291457 and EP0550308, and French Patent FR2622197 have developed a number of different types of transparent polyamides.
[0005] In recent years, with the increasing domestic demand, many enterprises and scientific research institutions have also conducted relevant research on transparent polyamide. Chinese patent CN105330843B discloses a semi-aromatic transparent nylon and its preparation method. The material is made of aromatic dibasic acid monomer, aliphatic dibasic acid monomer, aliphatic diamine monomer and transparent agent, with Tg of 119-122.5℃ and light transmittance of 85-95%. Chinese invention CN108047444A discloses a semi-aromatic transparent copolymer polyamide material and its preparation method. Transparent polyamide is obtained by copolymerization of terephthalic acid, decanediamine and dodecanedioic acid or tetradecanedioic acid. It has good heat resistance, excellent tensile toughness, low water absorption, Tg of about 60-80℃, and light transmittance of up to 91.7%. Chinese invention CN108047444A discloses a semi-aromatic transparent polyamide material and a preparation method thereof. The material is prepared by melt polycondensation of semi-aromatic amide salts (nylon 9T salt, 9I salt, 10T salt, 10I salt), aliphatic amide salts (nylon 610 salt, nylon 1010 salt) and necessary additives. The Tg is about 90-110°C and the transmittance is 85-90%.
[0006] From the above reports, it can be known that in order to make polyamide materials transparent, it is necessary to change or inhibit their crystallization through physical or chemical methods. The physical method is to add a crystal nucleating agent to make the crystal size fine. When the crystal size is reduced to below the wavelength of visible light, a transparent product can be obtained, which is also called microcrystallization. The transparent product obtained by this method has limited transparency and the transmittance cannot reach a high level. The chemical method is to select monomers with branched or cyclic structures for copolymerization. These monomers destroy the regularity of the molecular chain and can greatly reduce the density of hydrogen bonds and crystallinity, thereby obtaining a polyamide material with good transparency.
[0007] Transparent polyamide has high transparency and good heat resistance, which will make it have higher use value. At present, the transparent polyamide products (SATPA) produced industrially in China have poor heat resistance, low Tg and low thermal stability. Therefore, it is of great significance to design and synthesize heat-resistant transparent polyetheramide materials. Summary of the invention
[0008] In view of the technical problems that existing industrial transparent polyamide products have poor heat resistance, low Tg, low thermal stability, etc., the present invention provides a preparation method and application of heat-resistant transparent polyether amide. The obtained product has high glass transition temperature and good transparency, and the raw materials of dicarboxylic acid monomers containing ether bonds are cheap and easy to obtain. There are a large number of benzene rings in the dicarboxylic acid structure, and the molecular chain has high rigidity, which gives the material good heat resistance.
[0009] The transparent polyether amide of the present invention is prepared by reacting a dicarboxylic acid monomer containing an ether bond with a diamine in a solvent to form a salt, and preparing the heat-resistant transparent polyether amide by melt polymerization or copolymerization of nylon salt with other nylon salts, and preparing the transparent polyether amide by melt polycondensation in one step. The obtained transparent polyether amide has good transparency, a transmittance of 90.9% under 560nm visible light, and a 5% thermal decomposition temperature of the polymer of 465°C or above under N2 atmosphere, and has good heat resistance and good solvent resistance in non-strong polar solvents. It has broad application prospects in the fields of optical instruments, pressure-resistant windows, observation mirrors, sports equipment, special lamp covers, etc.
[0010] The present invention is achieved through the following technical solutions:
[0011] A method for preparing a heat-resistant transparent polyether amide comprises the steps of: using a dicarboxylic acid monomer and a diamine monomer to react in a salt-forming solvent, and then melt-polymerizing one or more nylon salts (i.e., nylon salt itself or with different types of nylon salts) to obtain the heat-resistant transparent polyether amide.
[0012] Furthermore, the dicarboxylic acid monomer is a dicarboxylic acid containing an ether bond, and the structure is as follows:
[0013]
[0014] Wherein, R is a polyaromatic ring group, preferably one of the following structures:
[0015]
[0016] Furthermore, the diamine monomer is an aliphatic diamine, an alicyclic diamine or an aromatic diamine; the aliphatic diamine includes one or more of butanediamine, pentanediamine, hexanediamine, nonanediamine, decanediamine, dodecyldiamine, etc.; the alicyclic diamine includes one or more of 4,4'-diamino-dicyclohexylmethane (PACM), 4,4'-diamino-dicyclohexylpropane, isophoronediamine (IPDA), 1,4-cyclohexanediamine (1,4-DCH), 1,4-cyclohexanedimethylamine, etc.; the aromatic diamine is preferably one or more of p-phenylenediamine, m-phenylenediamine, etc.
[0017] Furthermore, the salt-forming solvent is one or a mixed solvent of water, ethanol, N,N'-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide. The organic solvent has a fast salt-forming speed and the solvent can also be recycled and reused.
[0018] Furthermore, the salt-forming reaction is carried out under nitrogen conditions, the molar ratio of the dicarboxylic acid monomer to the diamine is 1:(1-1.02), the total mass ratio of the dicarboxylic acid monomer and the diamine to the solvent mass is 1:4-8, the reaction temperature is 65-90°C, and the pH value is 7.2-7.5 as the reaction endpoint.
[0019] Furthermore, the specific method of the melt polymerization is as follows: one or more nylon salts and 10 to 50% of the mass of the nylon salts of water are put into a reactor, the air in the reactor is replaced with high-purity nitrogen several times, the temperature is raised to 210 to 240°C, the pressure in the reactor is maintained at 1.5 to 4 MPa, and after maintaining the pressure for 1 to 5 hours, the air is released to normal pressure, and the temperature is continued to be raised to 240 to 300°C, and then gradually vacuumed, reacted for 0 to 5 hours, and the heat-resistant transparent polyetheramide resin is obtained by discharging the material.
[0020] The heat-resistant transparent polyetheramide obtained by the above method can be used to prepare products such as eyeglass frames, windshields, instrument panel covers, etc.
[0021] The beneficial effects of the present invention are:
[0022] The present invention is prepared in one step by melt polycondensation. The obtained transparent polyether amide has good transparency, and the transmittance under 560nm visible light can reach 90.9%. In an N2 atmosphere, the 5% thermal decomposition temperature of the polymer can reach above 465°C. It has good heat resistance and good solvent resistance in non-strong polar solvents.
[0023] The present invention designs and synthesizes a heat-resistant transparent polyether amide from the perspective of molecular design. The transparent polyether amide prepared by the present invention not only has a high glass transition temperature and transparency, but also the raw materials of the dicarboxylic acid monomer containing an ether bond are cheap and easily available, a large number of benzene rings exist in the dicarboxylic acid structure, and the molecular chain has high rigidity, which gives the material good heat resistance and excellent thermal stability, overcomes the defects of insufficient heat resistance and poor thermal stability of existing products, and can be widely used in products such as eyeglass frames, windshields, instrument panel covers, optical instruments, pressure-resistant windows, observation mirrors, sports equipment, special lamp covers and the like. DETAILED DESCRIPTION
[0024] The present invention is further illustrated below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the content of the present invention still fall within the scope of protection of the present invention.
[0025] Product performance characterization method:
[0026] Transmittance test: The thin sheet samples were prepared by hot pressing method, the sample thickness was about 1 mm, and the transmittance of visible light to the sample was measured by CARY60 UV-visible spectrophotometer.
[0027] Phase transition behavior test: The phase transition temperature of the sample was measured by a DSC-Q10 differential scanning calorimeter. In a nitrogen atmosphere, the heating and cooling rates were 10°C / min, first from 25°C to 300°C; then from 300°C to 25°C; then from 25°C to 300°C. The first heating was to eliminate the thermal history of the sample, and the Tg of the sample was obtained using the second heating curve.
[0028] Thermal stability test: The decomposition temperature of the polymer was tested by A-Q50 thermogravimetric analyzer of TA Company, USA. The test sample weight was about 3 mg, and the heating rate was 10°C / min, from 25-700°C.
[0029] Relative viscosity characterization: According to GB / T 12006.1-2009, 0.2500±0.0002g of polymer sample was dissolved in 96% sulfuric acid to prepare a 5g / L solution. The solution was tested using an Ubbelohde viscometer and the intrinsic viscosity value [η] was obtained by the one-point method. The test temperature was 25.00±0.05℃.
[0030] Example 1
[0031] (1) First, 2,2-bis[4-(4-carboxyphenoxy)phenyl]propane (1 mol, 468 g, referred to as M) and diaminobutane (1 mol, 88 g) were placed in a glass reactor, and then 2200 mL of DMF was added. The mixture was stirred (150 rpm / min), purged with nitrogen, and the air was exhausted. The temperature was raised to 65° C. After the pH value of the reaction system showed no significant change, the pH value was adjusted to about 7.3. The reaction was continued for 1 h, the material was discharged, filtered, washed, and dried to obtain nylon 4M salt.
[0032] (2) 100 g of nylon 4M salt and 40 mL of water were put into a reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 220-230°C, and the pressure in the reactor was maintained at 1.8-2.5 MPa (the temperature control accuracy of the electric heating jacket reactor was about ±5°C, and the pressure change in the reactor was controlled by venting, so the temperature and air pressure fluctuated slightly). The pressure was maintained for 4 hours, and the air was vented to normal pressure to discharge the water in the system. The temperature was continued to be raised to about 280°C, and then the system was gradually evacuated to reduce the pressure to -0.08 MPa. The reaction was continued for 1.5 hours, and nitrogen was filled, discharged, and cooled to obtain transparent polyether amide PA4M.
[0033] Example 2
[0034] (1) First, 2,2-bis[4-(4-carboxyphenoxy)phenyl]propane (1 mol, 468 g) and hexamethylenediamine (1 mol, 116 g) were placed in a glass reactor, and then 2400 mL of DMF was added. The reactor was stirred (200 rpm / min), and nitrogen was first purged into the reactor to exhaust the air. The temperature was raised to 65° C. After the pH value of the reaction system showed no obvious change, the pH value was adjusted to about 7.2. The reaction was continued for 1 h, the material was discharged, filtered, washed, and dried to obtain nylon 6M salt.
[0035] (2) 100 g of nylon 6M salt and 50 mL of water were put into a reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 220-230°C, and the pressure in the reactor was maintained at 2-2.6 MPa for 3 h. The pressure was vented to normal pressure to discharge the water in the system. The temperature was continued to be raised to about 290°C, and then the system was gradually vacuumed to reduce the pressure to -0.06 MPa. The reaction was continued for 3 h. The reactor was filled with nitrogen, discharged, and cooled to obtain transparent polyether amide PA6M.
[0036] Example 3
[0037] (1) First, 2,2-bis[4-(4-carboxyphenoxy)phenyl]propane (1 mol, 468 g) and decanediamine (1 mol, 172 g) were placed in a glass reactor, and then 3200 mL of DMF was added. The mixture was stirred (200 rpm / min), purged with nitrogen, and the air was exhausted. The temperature was raised to 70°C. After the pH value of the reaction system showed no significant change, the pH value was adjusted to about 7.5. The reaction was continued for 1 h, the material was discharged, filtered, washed, and dried to obtain nylon 10M salt.
[0038] (2) 100 g of nylon 10M salt and 30 mL of water were put into a reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 220-230°C, and the pressure in the reactor was maintained at 1.7-2.3 MPa. After maintaining the pressure for 3 hours, the air was vented to normal pressure to discharge the water in the system, and the temperature was continued to be raised to 280°C. Then, the system was gradually evacuated to reduce the pressure to -0.07 MPa, and the reaction was continued for 2.5 hours. The reaction was then discharged by nitrogen and cooled to obtain transparent polyether amide PA10M.
[0039] Example 4
[0040] (1) First, 2,2-bis[4-(4-carboxyphenoxy)phenyl]propane (1 mol, 468 g) and 4,4'-diamino-dicyclohexylmethane (1 mol, 210 g) were placed in a glass reactor, and then 4700 mL of NMP was added. Stirring (130 rpm / min), nitrogen was purged, and the air was exhausted. The temperature was raised to 75° C. After the pH value of the reaction system showed no obvious change, the pH value was adjusted to about 7.2, and the reaction was continued for 1 h. The material was discharged, filtered, washed, and dried to obtain nylon PACMM salt.
[0041] (2) 100 g of nylon PACMM salt and 20 mL of water were placed in a reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 220-230°C, and the pressure in the reactor was maintained at 1.5-2.2 MPa. The pressure was maintained for 3 h, and the air was vented to normal pressure to discharge the water in the system. The temperature was continued to be raised to about 290°C, and then the system was gradually vacuumed to reduce the pressure to -0.09 MPa. The reaction was continued for 1 h, and nitrogen was filled, discharged, and cooled to obtain transparent polyether amide PACMM.
[0042] Example 5
[0043] Take 70g of nylon 6M salt, 30g of nylon 10M salt and 35mL of water into a high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 5 times, heat up to 220-230°C, maintain the pressure in the reactor at 1.8-2.5MPa, maintain the pressure for 4h, vent to normal pressure to discharge the water in the system, continue to heat to 270°C, react at normal pressure for 1h, then gradually evacuate to reduce the system pressure to -0.09MPa, react for 2h, fill with nitrogen, discharge and cool to obtain transparent polyether amide 6M / 10M (7 / 3).
[0044] Example 6
[0045] Take 50g of nylon 6M salt, 50g of nylon PACMM salt and 20mL of water into a high-pressure reactor, replace the air in the reactor with high-purity nitrogen for 5 times, raise the temperature to 200-220°C, maintain the pressure in the reactor at 1.3-2MPa, maintain the pressure for 3.5h, vent to normal pressure to discharge the water in the system, continue to heat to 280°C, react at normal pressure for 0.5h, then gradually evacuate to reduce the system pressure to -0.06MPa, react for 3h, fill with nitrogen, discharge, and cool to obtain transparent polyether amide 6M / PACMM (5 / 5).
[0046] Example 7
[0047] (1) Isophthalic acid (1 mol, 166 g) and hexamethylenediamine (1 mol, 116 g) were first placed in a glass reactor, and then 560 mL of DMF was added. The mixture was stirred (150 rpm / min), purged with nitrogen, and the air was exhausted. The temperature was raised to 60°C. After the pH value of the reaction system showed no significant change, the pH value was adjusted to about 7.2. The reaction was continued for 1 h, and the mixture was filtered, washed, and dried to obtain nylon 6I salt.
[0048] (2) 90 g of nylon 6M salt, 10 g of nylon 6I salt and 30 mL of water were put into a high-pressure reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 200-210° C., and the pressure in the reactor was maintained at 1.2-1.8 MPa. After maintaining the pressure for 3 hours, the air was released to normal pressure to discharge the water in the system, and the temperature was continued to be raised to 280° C., and the reaction was carried out at normal pressure for 0.5 hour. Then, the system was gradually evacuated to reduce the pressure to -0.08 MPa, and the reaction was carried out for 1.5 hours. The system was filled with nitrogen, discharged and cooled to obtain transparent polyether amide PA6M / 6I (9 / 1).
[0049] Example 8
[0050] (1) First, terephthalic acid (1 mol, 166 g) and decanediamine (1 mol, 172 g) were placed in a glass reactor, and then 1300 mL of water was added. The mixture was stirred (200 rpm / min), purged with nitrogen, and the air was exhausted. The temperature was raised to 90°C. After the pH value of the reaction system showed no significant change, the pH value was adjusted to about 7.2. The reaction was continued for 1 h, the material was discharged, filtered, washed, and dried to obtain white nylon 10T salt.
[0051] (2) 80 g of nylon 10M salt and 20 g of nylon 10T salt and 50 mL of water were put into a high-pressure reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 230-240° C., and the pressure in the reactor was maintained at 2.3-3 MPa. After maintaining the pressure for 4 hours, the air was released to normal pressure to discharge the water in the system, and the temperature was continued to be raised to 270° C., and the reaction was carried out at normal pressure for 0.5 hours. Then, the system was gradually evacuated to reduce the pressure to -0.07 MPa, and the reaction was carried out for 2 hours. The system was filled with nitrogen, discharged, and cooled to obtain transparent polyamide PA10M / 10T (8 / 2).
[0052] Example 9
[0053] 30g of caprolactam, 70g of nylon 6M salt and 40mL of water were put into a high-pressure reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 220°C, and the pressure in the reactor was maintained at 1.5-2MPa. After maintaining the pressure for 3h, the air was vented to normal pressure to discharge the water in the system, and the temperature was continued to be raised to 275°C. The reaction was carried out at normal pressure for 1h, and then the system was gradually evacuated to reduce the pressure to -0.09MPa. The reaction was carried out for 1.5h, and nitrogen was filled, discharged and cooled to obtain transparent polyamide PA6 / 6M (3 / 7).
[0054] Example 10
[0055] 10g of nylon 66 salt, 90g of nylon 6M salt and 20mL of water were put into a high-pressure reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 210°C, and the pressure in the reactor was maintained at 1-1.6MPa. After maintaining the pressure for 2.5h, the air was vented to normal pressure to discharge the water in the system, and the temperature was continued to be raised to 275°C. The reaction was carried out at normal pressure for 1.5h, and then the system was gradually evacuated to reduce the pressure to -0.08MPa. The reaction was carried out for 1h, and nitrogen was filled, discharged, and cooled to obtain transparent polyamide PA66 / 6M (1 / 9).
[0056] Embodiment 11
[0057] (1) Isophthalic acid-type dicarboxylic acid 4,4'-(1,3-phenylenebis(oxy))dibenzoic acid (1 mol, 350 g, referred to as D) and hexamethylenediamine (1 mol, 116 g) were placed in a glass reactor, and 2000 mL of DMF was added. Stirring (100 rpm / min) was started, nitrogen was passed through the reactor to exhaust the air, and the temperature was raised to 70°C. After the pH value of the reaction system showed no significant change, the pH value was adjusted to about 7.2, and the reaction was continued for 1 hour. The product was discharged, filtered, washed, and dried to obtain nylon 6D salt.
[0058] (2) 100 g of nylon 6D salt and 50 mL of water were put into a reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 200-210° C., and the pressure in the reactor was maintained at 1.5-2.1 MPa. The pressure was maintained for 3 h, and the air was vented to normal pressure to discharge the water in the system. The temperature was continued to be raised to about 280° C., and then the system was gradually evacuated to reduce the pressure to -0.09 MPa. The reaction was continued for 2 h, and nitrogen was filled, discharged, and cooled to obtain transparent polyether amide PA6D.
[0059] Example 12
[0060] (1) Diphenyl ether type dicarboxylic acid 4,4'-((oxybis(4,1-phenylene))bis(oxy))dibenzoic acid (1 mol, 442 g, referred to as F) and decanediamine (1 mol, 172 g) were placed in a glass reactor, and 2700 mL of DMSO was added. The reactor was stirred (130 rpm / min), nitrogen was purged into the reactor, and the air was exhausted. The temperature was raised to 70° C. After the pH value of the reaction system showed no significant change, the pH value was adjusted to about 7.5, and the reaction was continued for 1 h. The product was discharged, filtered, washed, and dried to obtain nylon 10F salt.
[0061] (2) 100 g of nylon 10F salt and 50 mL of water were placed in a reactor, and the air in the reactor was replaced with high-purity nitrogen for 5 times. The temperature was raised to 210-220°C, and the pressure in the reactor was maintained at 1.5-2.3 MPa. The pressure was maintained for 3 h, and the air was vented to normal pressure to discharge the water in the system. The temperature was continued to be raised to about 270°C, and then the system was gradually vacuumed to reduce the pressure to -0.09 MPa. The reaction was continued for 1 h, and nitrogen was filled, discharged, and cooled to obtain transparent polyether amide PA10F.
[0062] Table 1 shows the properties of transparent polyether amide obtained in some examples
[0063]
[0064] Table 2 shows the solubility of some of the obtained polymers
[0065]
[0066] Note: ++: soluble at room temperature; +: soluble when heated; -: swells at room temperature; --: insoluble when heated.
Claims
1. A method for preparing a heat-resistant transparent polyether amide, characterized in that: The heat-resistant transparent polyether amide is obtained by using a dicarboxylic acid monomer and a diamine monomer to react in a salt-forming solvent, and then melt-polymerizing one or more nylon salts. The dicarboxylic acid monomer is a dicarboxylic acid containing an ether bond, and the structure is as follows: , R is one of the following structures: , The diamine monomer is an aliphatic diamine or an alicyclic diamine; The salt-forming solvent is one or a mixed solvent of two or more selected from water, ethanol, N,N'-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide; The salt-forming reaction is carried out under nitrogen conditions, the molar ratio of the dicarboxylic acid monomer to the diamine is 1: (1-1.02), the total mass ratio of the dicarboxylic acid monomer and the diamine to the solvent mass is 1:4-8, the reaction temperature is 65-90° C., and the pH value is 7.2-7.5 as the reaction end point; The specific method of the melt polymerization is as follows: one or more nylon salts and water that accounts for 10-50% of the mass of the nylon salts are put into a reactor, the air in the reactor is replaced with high-purity nitrogen for several times, the temperature is raised to 210-240° C., the pressure in the reactor is maintained at 1.5-4 MPa, and after maintaining the pressure for 1-5 hours, the air is released to normal pressure, the temperature is continued to be raised to 240-300° C., and then vacuum is gradually drawn, the reaction is carried out for 0-5 hours, and the heat-resistant transparent polyetheramide resin is obtained by discharging the material.
2. The method for preparing the heat-resistant transparent polyether amide according to claim 1, characterized in that: The aliphatic diamine includes one or more of butanediamine, pentanediamine, hexanediamine, nonanediamine, decanediamine, and dodecyldiamine; the alicyclic diamine includes one or more of 4,4'-diamino-dicyclohexylmethane, 4,4'-diamino-dicyclohexylpropane, isophoronediamine, 1,4-cyclohexanediamine, and 1,4-cyclohexanedimethylamine.
3. Use of the heat-resistant transparent polyetheramide obtained by the method according to claim 1 or 2 in the preparation of eyeglass frames, windshields, instrument panel covers, optical instruments, pressure-resistant windows, observation mirrors, sports equipment or special lamp covers.
Citation Information
Patent Citations
A semi-aromatic transparent nylon and its preparation method
CN105330843B
Semi-aromatic transparent copolymer polyamide material and preparing method thereof
CN108047444A
Transparent compositions with high resistance to chemical agents
EP0550308A1
Polyamide moulded masses containing semi-crystalline transparent copolyamides for producing highly flexible transparent moulded parts with high notch-impact strength, low water absorbency and excellent resistance to chemicals
EP2291457A2
Transparent polyamides and their method of production.
FR2622197A1